Ecological control line: A decade of exploration and an innovative path of ecological land management for megacities in China. (15th April 2017) - Hong, Wuyang; Yang, Chengyun; Chen, Liuxin; Zhang, Fangfang; Shen, Shaoqing; Guo, Renzhong
Abstract: Ecological control line is a system innovation in the field of ecological environment protection in China and it has become as an important strategy of national ecological protection. Ten years have passed since the first ecological control line in Shenzhen was delimited in 2005. This study examines the connotations of ecological control line and the current study status in China and abroad, and then takes a brief description about the delimitation background and existing problems of the ecological control line in Shenzhen. The problem-solving strategy is gradually transforming from extensive management to refined management. This study proposes a differential ecological space management model that merges the space system, management system, and support system. The implementation paths include the following five aspects: delimiting ecological bottom lines to protect core ecological resources; formulating access systems for new construction projects to strictly control new construction; implementing construction land inventory reclamation assisted by market means; regulating boundary adjusting procedures and processes; and constructing ecological equity products by using multiple means to implement rights relief. Finally, this study illustrates the progress of the implementation and discusses the rigorousness and flexibility problems of ecological control line and calls for the promotion of the legislation. The management model and implementation paths proposed in this study have referential significance for developing countries and megacities to achieve ecological protection and sustainable development. Highlights: Ecological control line is a system innovation in the field of ecological environment protection in China. Framework of ecological control line management model includes the space, management, and support systems. Implementation paths with operability are proposed. Both rigorousness and flexibility should be considered for effective management. Judgment on whether ecological controls limit economic development is discussed.